Effect of Essential Microelements on Proteomic Profile of Lamb Muscle Tissue Protein - Tatiana M. Giro; Andrey V. Kulikovsky; Anna V. Giro (Техника и технология пищевых производств, 2023)
Proteomic technologies make it possible to evaluate the composition of meat raw materials at different stages of processing. Proteomic studies of lamb muscle tissue help to expand scientific knowledge about the effect of essential organic microelements on the interaction of lamb muscle tissue proteins. The research objective was to identify and quantify lamb muscle tissue proteins from young sheep grown on feed additives fortified with microelements. The research featured meat from young sheep of the Edilbaev breed aged 7 months that consumed additives Yoddar-Zn and DAFS-25 as part of their diet. The experiment lasted 105 days. The microelement composition of lamb muscle tissue underwent atomic absorption spectrometry. The proteomic profile was identified using O'Farrell’s two-dimensional gel electrophoresis (2-DE) with isoelectrofocusing in ampholine (IEF-PAGE). Aluminum, iodine, silicon, selenium, and zinc were identified in lamb samples from young sheep that received feed additives Yoddar-Zn and DAFS-25 for 105 days. Major protein fractions included eight with a molecular weight of 12–15 kDa, 42 with 16–30 kDa, and 45 with 35–110 kDa (pI 5.0–8.0). The samples contained glutathione-S-transferase, which is responsible for biotransformation of toxic compounds, maintenance of intracellular homeostasis, and stress resistance. All the experimental samples had triose phosphate isomerase (glycolysis enzyme). The tests also revealed superoxide dismutase, which catalyzes the superoxide radical into peroxides and oxygen, thus protecting body cells from free oxygen radicals. The research provided relevant data on the effect of innovative feed additives on the molecular mechanisms that occur in mutton muscle tissue and affect the proteomic profile of meat proteins and electrophoretic activity. The feed additives with organic microelements proved efficient. The results can be used to model and adjust autolysis in order to obtain meat with the necessary technological properties.